Web-Based Design of School Information Systems at SMA Madani Depok - Septyan Dwianto; Jejen Jaenudin; Fitria Rachmawati (Institute of Computer Science (IOCS), 2022)
School Information System Design In Smk WEB-BASED MADANI DEPOK. SMK Madani Depok is an educational institution engaged in educational services that is currently improving the performance of the institution. SMK Madani Depok is located at JL. Mandor Samin RT. 02/06 Ex. Kalibaru District. Cilodong, Depok City, which has a duty in Education Services. In carrying out this task, SMK Madani Depok has several school data or report documents, such as student data, teacher data, subject data, majors and some activity information. However, so far there have been shortcomings in terms of data processing and how to convey information to parents as guardians of students, because at SMK Madani Depok there are still a lot of manual systems. To overcome this problem, a new system is needed that makes it easier to process data and reports, so as to minimize errors in data and information management. The design of a web-based school information system for SMK Madani Depok is one solution to improve the quality of education services. With this service can make it easier to manage data processing and reports. This information system is designed using PHP and MySQL, and this information system is connected to the user who can provide information to the user.